HIGH LEVEL OF SECURITY AND CONTINUOUS MONITORING FOR ANALYZING SMART CONTRACT BEHAVIORS - Sangeetha R; Veena M N (International Journal of Research -GRANTHAALAYAH, 2025)
"Smart contracts" are software documented on block chains under specific circumstances that control the allocation of assets between individuals. In a smart healthcare supply chain, product traceability is a major issue. Two enabling technologies in the smart healthcare supply chain that ensure product traceability and safeguard against data manipulation are block chain and smart contracts. A smart contract workflow must be developed and carried out in a block-chain-based supply chain in accordance with the input data. This paper has an objective function to meet the entire system as a parallel composition of smart contracts and users this paper analyze the behavior of smart contracts and a core language of programs with an essential set primitive. The experimental results show that the proposed method can accurately detect security vulnerabilities and logic flaws in smart contracts through formal verification and other analysis techniques before smart contracts are deployed.